PENGARUH KEBIJAKAN PENGHAPUSAN SANKSI PAJAK DAN KEPATUHAN WAJIB PAJAK DALAM MELAPORKAN SPT TAHUNAN TERHADAP PENERIMAAN PAJAK PENGHASILAN ( STUDI KASUS WAJIB PAJAK BADAN YANG TERDAFTAR DI KANTOR PELAYANAN PAJAK PRATAMA BANDA ACEH TAHUN 2014-2015) - Al Kautsar; Adnan Adnan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The purpose of this study was to examine the effect of the elimination of tax penalties and tax compliance in reporting annual tax return, the income tax revenues on corporate taxpayers registered in the tax office pratama Banda Aceh in 2014-2015.The method used in this study is simple random sampling. The sample in this research is the acceptance of corporate taxpayers and who obtain the removal of tax sanctions on the tax office in Banda Aceh. A total of 50 corporate taxpayers registered in the tax office in Banda Aceh year 2014-2015. The results of this study indicate that (1) the removal of sanctions taxes and tax compliance in reporting annual tax return simultaneously affected the tax revenue (2) the removal of sanctions the tax does not affect the tax revenue (3) tax compliance in reporting annual tax return affect the income of tax revenue